A three dimensional performance analysis of a developed evacuated tube collector using a CFD fluent solar load model - Ali, B.H. (EDP Sciences, 2014)
For the flow through type selected geometry of the designed evacuated tube collector ETC, a three dimensional simulation and analysis of the thermal performance was done, using the ray-tracing solar load model provided by the ANSYS-FLUENT software. In this model the solar radiation heat flux is solved using fair weather condition radiation equations, and then solar radiation load is considered as a heat source term in the energy equation. The thermal effects of the fluid flow and heat transfer in the collector, temperature fields as well as the solar radiation distribution, and other related factors under the different conditions have been discussed and analyzed. Â© 2014 Owned by the authors, published by EDP Sciences.